ANALISIS PERSAMAAN LENGKUNG DEBIT PADA POS DUGA AIR DI HULU SUNGAI WADUK KEDUNGOMBO - Kresfiaprilianto, Ananda Dwi Setiawan; Wahyudi, Slamet Imam; Ni”™am, Moh Faiqun (Politeknik Negeri Semarang, 2023)
Kedungombo reservoir is the largest reservoir in the Serang-Lusi watershed, Jratunseluna river basin, Central Java. Water level and discharge in the upstream river entering the reservoir were measured at 3 Gauging Stations (AWLR Guwo -Serang River, AWLR Jengglong - Laban River, and AWLR Girimargo - Uter River).The objective of this research is to determine the river's cross section, analyse changes in water level, calculate the equation for the rating curve, and assess the accuracy of the present equations at the observation site.The discharge curve analysis (Rating curve) was carried out using logarithmic analysis based on references from WMO, WSC and the Ministry of Public Works and Housing. This rating curve will describe the relationship of water level measurement to the observed river discharge.Measurements of river flow and cross-section in 2022 were carried out to add historical data on water level fluctuations as well as previous discharge measurements. The rating curve equations for the three gauging stations that were observed sequentially were Guwo station (Q = 13.23*(H+0.6)^2.432), Jengglong station (Q = 15.536*(H+0.2)^2.505) and Girimargo station (Q = 17,128*(H+0.0)^2,203). The rating curves that have been calculated indicate low accuracy at low water level due to the presence of scour and fill at the bottom of the cross-section with correlation values and RMSE respectively: PDA Guwo (R = 0.998 and RMSE = 1.62), PDA Jengglong (R = 0.985 and RMSE = 0.44), and PDA Girimargo (R = 0.961 and RMSE = 1.00).